Perception and Expectation of Tourists Toward the Accommodation Services in Rural Tourism Penglipuran Bangli - Ratih Pertiwi, Putu; Diah Kesumadewi, Putu; Trisna Eka Putri, Ida Ayu (Udayana Journal of Social Sciences and Humanities, 2018)
This research aims to know the perception and the expectation of tourists toward the accommodation services in Penglipuran Rural Tourism. In the development of rural tourism as an alternative tourism development approach, tourists who are expected to come not only to enjoy the natural beauty and the culture of the community. But also to stay more than a day so that can be directly involved with the culture of the local community, in accordance to the concept of rural tourism. Therefore, accommodation services play such an important role to provide a pleasant stay for the tourists through the facilities dan their services, likewise in Penglipuran Rural Tourism. To discover it, necessary data from several tourists who stayed in accommodation of Penglipuran Rural Tourism used as samples. Analyzed using descriptive qualitative analysis technique where Likert Scale Analysis is needed to determine the perception of the tourists toward the accommodation in Penglipuran Rural Tourism,Importance-Performance Analysis used to determine the expectation of the tourists, and 7Ps of marketing mix used as the indicators. As the result, the perception and the expectation of the tourists toward the accommodation services in Penglipuran Rural Tourism, both of guesthouse and homestay have the average scores as perception (4,16) and expectation (4,16) from 22 indicators of services, it shows that the performance generally in accordance with the tourists’ expectation. Based on the priority level, all indicators have the same level of satisfaction (100%), it means all indicators have the same priority either on guesthouse accommodation services or homestay accommodation services. The suggestion that can be given from this research to the administrator of Penglipuran Rural Tourism is to maintain and improve the service that they deliver to the tourists in order to provide a pleasant stay for them when they are in Penglipuran Rural Tourism.